Efeito da música na melhoria da qualidade de vida em pacientes com câncer de mama em tratamento quimioterápico - LIMA, Talita Uchoa (2019)
Introduction: Breast cancer is the most common tumor among women. Its treatment can determine adverse effects, which added to the disease process can bring feelings of distress and anxiety. Thus, health-related quality of life measures has been sought, and the implementation of music can bring physiological effects and may control symptoms of cancer treatment. Objective: To verify the effects of music stimulation on the reduction of adverse symptoms in breast cancer patients undergoing chemotherapy. Methods: Randomized, undercover clinical trial conducted in São Luís Hospitals between October 2017 and May 2019. Women with breast cancer undergoing chemotherapy, followed in the first 3 treatment cycles, were included. Patients were randomized into groups: GM (Music Group) and GC (Control Group). The collection consisted of an interview with data: Demographic / Economic Partner, Quality of Life (WHOQOL-bref), Beck Depression Inventory - 2nd Ed (BDI-II), Beck Anxiety Inventory (BAI) and Chemotherapy Toxicity Scale - ETQ. Patients were evaluated in three phases: Initial Phase (first chemotherapy session), Intermediate Phase (second chemotherapy session) and Final Phase (third chemotherapy session). In GM music was applied with an MP3 device, using headphones, for a period of 30 minutes, before the application of chemotherapy; In the CG there was no intervention beyond the completion of the questionnaires. The data analyzed in the SPSS (version 22), through the tests of: Shapiro Wilk, Student's t and chi square at an alpha significance level of 0.05 or less. Results: Twenty-three patients were included in the study and divided into two assessment groups. The groups are homogeneous in terms of socioeconomic, clinical characteristics and lifestyle habits. Higher quality of life scores on the GM functional scale were observed in relation to the CG both in the first session (17.2 ± 1.2 vs 15.3 ± 1.9, respectively) and in the third chemotherapy session (16.1 ± 1.9 vs 14.4 ± 1.9, respectively), p <0.05. Depression scores showed statistically significant differences between groups in the third chemotherapy session (GM, 5.5 ± 3.9 vs 21.1 ± 6.6 points in the CG). Anxiety scores showed a statistically significant difference between the groups in the third chemotherapy session (9.8 ± 6.7 vs 20.3 ± 10.1 in the GM and CG groups, respectively). There was no statistically significant difference regarding the adverse effects evaluated by the Chemotherapy Toxicity Scale when comparing the GM and CG in the second and third chemotherapy sessions. Regarding the subject's subjective impression questionnaire, all eight GM patients reported positive changes in life with musical application, and the changes mentioned were mood improvement (2 patients), motivation (2 patients), self-confidence (2 patients), relationship (1 patient) and self-esteem (1 patient). There were no negative symptoms reported with the music. All patients reported improvement in tiredness or fatigue (mean 7.12 on a scale from 0 to 10), as well as improvement in stress (average 7.87 on a scale from 0 to 10). Conclusion: there was an improvement in the quality of life, anxiety and depression scores, which brings us to the positive effect of music on the adverse effects of cancer treatment, revealing that this is a low cost, simple and affordable strategy in the adjunctive treatment of cancer patients.